2016
DOI: 10.1017/s0007114516003858
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated bitter compounds (from Gentiana lutea) reduce daily energy intakes in humans

Abstract: Mounting evidence showed that bitter-tasting compounds modulate eating behaviour through bitter taste receptors in the gastrointestinal tract. This study aimed at evaluating the influence of microencapsulated bitter compounds on human appetite and energy intakes. A microencapsulated bitter ingredient (EBI) with a core of bitter Gentiana lutea root extract and a coating of ethylcellulose-stearate was developed and included in a vanilla microencapsulated bitter ingredient-enriched pudding (EBIP). The coating mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 37 publications
1
45
0
1
Order By: Relevance
“…In another study, bitter secoiridoids from the Gentiana lutea root were tested in a microencapsulated formulation mixed into a vanilla pudding, and administered to healthy subjects. Concentrations of gut hormones, including GLP-1, GIP and PYY, were not significantly different after eating pudding containing microencapsulated bitter ingredients compared with control pudding, although subsequent energy intake was reduced [66] . Taken together with the duodenal infusion studies, however, the results do not suggest that bitter substances will provide a strong encapsulatable stimulus for targeting GLP-1 and PYY secretion.…”
Section: Stimulus Delivery To the Distal Gut By Delayed Release Formumentioning
confidence: 79%
“…In another study, bitter secoiridoids from the Gentiana lutea root were tested in a microencapsulated formulation mixed into a vanilla pudding, and administered to healthy subjects. Concentrations of gut hormones, including GLP-1, GIP and PYY, were not significantly different after eating pudding containing microencapsulated bitter ingredients compared with control pudding, although subsequent energy intake was reduced [66] . Taken together with the duodenal infusion studies, however, the results do not suggest that bitter substances will provide a strong encapsulatable stimulus for targeting GLP-1 and PYY secretion.…”
Section: Stimulus Delivery To the Distal Gut By Delayed Release Formumentioning
confidence: 79%
“…Many studies have suggested that single pharmacological compounds that are isolated from natural plants have positive therapeutic effects on herbal medicines [ 9 , 10 ].The root of Gentiana lutea L. (GL) has been used to improve gastrointestinal motility and liver function as a herbal medicine [ 11 ]. Additionally, a recent study reported that GL is effective for body weight control in overweight individuals by reducing their daily energy intake [ 12 ]. Physiological bioactive compounds that have been isolated from GL have been identified, such as iridoids (loganic acid), secoiridoids (gentiopicroside, sweroside, swertiamarin, and amarogentin), and xanthones (isogentisin) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Out of 32 analyzed studies, 16 (50%) did not report adverse events at all. In 10 of the remaining 16 trials, none of the tested plant extracts caused an adverse event [15,48,49,54,56,64,68,70,71,76]. Six studies [51,58,63,66,67,74] reported mild adverse events such as gastrointestinal distress (e.g., dyspepsia, flatulence, diarrhea, or constipation), skin rash, or headache.…”
Section: Resultsmentioning
confidence: 99%
“…In multiple studies that recorded the outcomes over several hours on just one or two days, respectively, participants were instructed to refrain from exercise 24 to 48 h before test day [28,51,60,61,62,65,75] and to arrive after an overnight fast at the test center [52,57,62,69,70,76,86]. The bioactive phytochemical was mostly taken with a standardized meal, varying from a breakfast meal with approximately 1150 kJ (275 kcal) [73] to a breakfast buffet with a total amount of approximately 32,962 kJ (7878 kcal) [61].…”
Section: Resultsmentioning
confidence: 99%